The Tale of Cuffy Bear - Bailey, Arthur Scott, 1877-1949; Smith, Harry L. (Illustrator) (Salt Lake City, UT : Project Gutenberg, 2005)
"The Tale of Cuffy Bear" by Arthur Scott Bailey is a children's storybook written in the early 20th century. This charming tale follows the antics of a young bear named Cuffy as he explores the woods around Blue Mountain, encounters various animals, and learns valuable lessons about behavior and the world. With its engaging storytelling and whimsical adventures, the book captures the innocence and curiosity of childhood. The story begins with Cuffy waking up after a long winter's sleep and enjoying the arrival of spring. His adventures include finding a porcupine, discovering a sugar-maple tree, and learning to swim with the help of his father, Mr. Bear. Throughout the tale, Cuffy's mischief often leads him into trouble, such as trying to capture a pig from Farmer Green's farm and getting chased by hornets. These humorous escapades, mixed with moments of reflection and growth, reveal Cuffy's character development as he learns about friendship, family, and the dangers of the wild. All of these experiences culminate in heartwarming lessons for both Cuffy and the readers, making the book an enjoyable read for children and adults alike. (This is an automatically generated summary.)
Release date is 2005-04-04
E-text prepared by Juliet Sutherland, Govert Schipper, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Animals -- Juvenile fiction; Bears -- Juvenile fiction